2023
DOI: 10.1007/s00784-023-05364-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and periodontal conditions of dental implants placed in free fibula flaps (FFF): a retrospective study with a mean follow-up of 6 years

Giorgio Lombardo,
Antonio D’Agostino,
Pier Francesco Nocini
et al.

Abstract: Objectives Up-to-date literature regarding long-term success of implant rehabilitations after microvascular reconstructions with free fibula flap (FFF) is still very scarce. This study aimed to evaluate clinical outcomes, especially related to oral hygiene conditions, of patients rehabilitated with this technique. Materials and methods A total of 25 patients who underwent maxillofacial reconstructive surgery with FFF were retrospectively evaluated for soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Placing conventional dental implants of standard diameters and lengths often requires additional bone augmentation with predictable increases in treatment morbidity, time, and cost [34][35][36]. It has been reported that clinicians must emphasize to patients and caregivers to provide customized patient prosthetic accessibility for oral hygiene procedures [37].…”
Section: Discussionmentioning
confidence: 99%
“…Placing conventional dental implants of standard diameters and lengths often requires additional bone augmentation with predictable increases in treatment morbidity, time, and cost [34][35][36]. It has been reported that clinicians must emphasize to patients and caregivers to provide customized patient prosthetic accessibility for oral hygiene procedures [37].…”
Section: Discussionmentioning
confidence: 99%
“…The current standard of care for reconstruction of defects involves surgical intervention utilizing autogenous bone grafts (autografts) due to their established osteoconductive, osteogenic, and osteoinductive properties [ 5 ]. This type of grafting has been used in a wide range of procedures, including alveolar distraction, dental implantation, and various head and neck procedures [ 6 , 7 , 8 ]. Autografts are harvested from various bones; however, the fibula is a common donor site due to its non-weight-bearing status [ 6 ].…”
Section: Introductionmentioning
confidence: 99%